Different Detection Methods of Blood Nucleic Acid and Enzyme-linked Immunosorbent Assay for Blood Virus Screening: Detection Methods of Blood Nucleic Acid and ELISA - Ma, Qingchuan; Xue, Junfang; Xin, Xiqin; Mu, Ni; Wu, Xi; Yang, Bing; Xu, Na; Du, Juan (Cellular and Molecular Biology, 2022)
Through the detection of antigens or antibodies of related viruses in blood, the incidence of transfusion-transmitted diseases can be reduced, the comprehensive performance indicators of the human body can be judged, and the disease can be effectively treated and prevented. The purpose of this study is to analyze the screening results of blood viruses by different detection methods of blood nucleic acid and enzyme-linked immunosorbent assay. In this study, the comparison and data analysis of the two detection methods in the study were carried out through the comparison method and data analysis method, and the functional analysis is combined with the detection principle. The positive rate of anti-HCV was 1.67% (10 / 600) by ELISA and 0.34% (2 / 590) by nucleic acid. Conclusion enzyme immunoassay is not sensitive to the antigen-antibody reaction in the window stage, and there is a mistake in the detection. However, nucleic acid detection has high sensitivity because of its PCR principle, but it is also prone to false-positive.